Chemometric Classification Techniques as a Tool for Solving Problems in Analytical Chemistry. (27th November 2019) - Bevilacqua, Marta; Nescatelli, Riccardo; Bucci, Remo; Magrì, Andrea D; Magrì, Antonio L; Marini, Federico
Abstract: Supervised pattern recognition (classification) techniques, i.e., the family of chemometric methods whose aim is the prediction of a qualitative responseon a set of samples, represent a very important assortment of tools for solving problems in several areas of applied analytical chemistry. This paper describes the theory behind the chemometric classificationtechniques most frequently used inanalytical chemistry together with some examples of their application to real-world problems.